Disrupting Reconsolidation by Systemic Inhibition of mTOR Kinase via Rapamycin Reduces Cocaine-Seeking Behavior - Zhang, Fushen; Huang, Shihao; Bu, Haiyan; Zhou, Yu; Chen, Lixiang; Kang, Ziliu; Chen, Liangpei; Yan, He; Yang, Chang; Yan, Jie; Jian, Xiaohong; Luo, Yixiao (Frontiers in Pharmacology, 2021)
Drug addiction is considered maladaptive learning, and drug-related memories aroused by the presence of drug related stimuli (drug context or drug-associated cues) promote recurring craving and reinstatement of drug seeking. The mammalian target of rapamycin signaling pathway is involved in reconsolidation of drug memories in conditioned place preference and alcohol self-administration (SA) paradigms. Here, we explored the effect of mTOR inhibition on reconsolidation of addiction memory using cocaine self-administration paradigm. Rats received intravenous cocaine self-administration training for 10 consecutive days, during which a light/tone conditioned stimulus was paired with each cocaine infusion. After acquisition of the stable cocaine self-administration behaviors, rats were subjected to nosepoke extinction (11 days) to extinguish their behaviors, and then received a 15 min retrieval trial with or without the cocaine-paired tone/light cue delivery or without. Immediately or 6 h after the retrieval trial, rapamycin (10 mg/kg) was administered intraperitoneally. Finally, cue-induced reinstatement, cocaine-priming-induced reinstatement and spontaneous recovery of cocaine-seeking behaviors were assessed in rapamycin previously treated animals, respectively. We found that rapamycin treatment immediately after a retrieval trial decreased subsequent reinstatement of cocaine seeking induced by cues or cocaine itself, and these effects lasted at least for 28 days. In contrast, delayed intraperitoneal injection of rapamycin 6 h after retrieval or rapamycin injection without retrieval had no effects on cocaine-seeking behaviors. These findings indicated that mTOR inhibition within the reconsolidation time-window impairs the reconsolidation of cocaine associated memory, reduces cocaine-seeking behavior and prevents relapse, and these effects are retrieval-dependent and temporal-specific.